2021
DOI: 10.1002/term.3175
|View full text |Cite
|
Sign up to set email alerts
|

Is percutaneous injection of bone marrow concentrate, demineralized bone matrix and PRF an alternative to curettage and bone grafting for treating aneurysmal bone cyst?

Abstract: To determine the efficacy and safety of a single injection with autologous bone marrow concentrate (BMC) combined with demineralized bone matrix (DBM) and platelet‐rich fibrin (PRF) compared to curettage and bone grafting for treating aneurysmal bone cysts (ABC). Two hundred thirty‐nine patients were treated with curettage and bone grafting (Curettage Group), and 21 with percutaneous injection of DBM associated with autologous BMC and PRF (DBM + BMC + PRF Group). All patients attended the outpatient clinic to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…In fact, we reported that the rate of recurrence after a single treatment was 19% in a series of 21 patients 30 …”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In fact, we reported that the rate of recurrence after a single treatment was 19% in a series of 21 patients 30 …”
Section: Discussionmentioning
confidence: 98%
“…Even if curettage with or without bone grafting persist to be the most widely used treatment for ABCs, [23][24][25] many surgical and nonsurgical options have been proposed over the years to reduce the risk of recurrence as high-speed bur, 16 large cortical window, 26 adjuvant therapy, 22,27,28 doxycycline foam ablation, 14,15 and bone marrow injection technique. 29,30 These new therapies are based on an improved understanding of the nonneoplastic nature of the lesion. However, until now, there was no consensus regarding the best procedure.…”
Section: Long-term Complication Ratementioning
confidence: 99%
See 1 more Smart Citation
“…2), systemic therapies, radiofrequency ablation, embolization, percutaneous injectable bone substitutes, wide resections, and if deemed necessary, a wide range of osteosynthesis. [2][3][4][13][14][15][16][17] Treatment strategies depend on location, size, symptoms, impending and present pathologic fractures, local considerations, and individual preferences. Because of this heterogeneity, there is no consensus or guideline.…”
Section: Discussionmentioning
confidence: 99%
“…1), bone marrow injections, cryotherapy, decompression, curopsy (ie, biopsy and curettage), curettage with or without filling and/or chemical adjuvants and/or high-speed burring (Fig. 2), systemic therapies, radiofrequency ablation, embolization, percutaneous injectable bone substitutes, wide resections, and if deemed necessary, a wide range of osteosynthesis 2–4,13–17. Treatment strategies depend on location, size, symptoms, impending and present pathologic fractures, local considerations, and individual preferences.…”
mentioning
confidence: 99%